Preparation for Nurse Licensure Examination in Adult Nursing Among Fourth-Year Nursing Students, Faculty of Nursing, a University in Southern Thailand - Thasaneesuwan, Samonnan; Narkthong, Natsayakarn; Chuaytaen, Thawinee; Mukpradab, Sasithorn; Puttakun, Nareerat (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
The Nurse Licensure Examination is a requirement for all student nurses graduating from the bachelor’s degree program in order to become a registered nurse in Thailand. Successfully passing the test on the first attempt helps the accreditation of nursing education institutions as well as their quality assurance. This qualitative study aimed to present how some Thai nursing students prepared themselves for the licensure examination as a part of the greater effort to develop a nurse licensure examination preparation model. Three focus group interviews were employed in the data collection, and the total sample consisted of twenty-seven nursing students. The content analysis method was used in the data analysis. The trustworthiness of the study was established in accordance with the Lincoln and Guba criteria. The analysis identified strategies, supportive factors and barriers related to the preparation for the nurse licensure examination. The strategies for preparation used by the participants were: studying on one’s own; using a tutorial peer support group, and tutoring by experts. The supportive factors were both internal and external. The internal factors are having a clear target, good planning, and self-discipline The external factors are recieving support from friends, support of senior students and support from e-Learning. Meanwhile, the identified barriers were: failure to manage time effectively and guessing the best choice on the written test. These findings depict the current situation regarding the preparation undertaken by nursing students for their nurse licensure examination as well as the associating supportive factors and barriers. They will be very valuable in developing new and more effective strategies for preparation in order to enable students to pass the examination successfully.